Instructional Supervision Management to Enhance Student Independence - Sobari; Dhita Annisa Fauzia; Dina Hairun Nissa; Gerry Pratama (al-Afkar, Journal For Islamic Studies, 2026)
Student independence is a key indicator of a successful educational process. Effective management of instructional supervision plays a strategic role in fostering independent learning among students. Planned and continuous supervision enables teachers to create a conducive learning environment, thereby encouraging students to take an active and responsible role in their learning. This study aims to analyze the role of instructional supervision management in enhancing student independence. A literature review method was employed, examining various relevant sources. The analysis indicates that effective instructional supervision can boost students' learning motivation and independence. Consequently, the proper implementation of instructional supervision management serves as an effective strategy for fostering student independence.